A COMPARATIVE ANALYSIS OF ENGLISH TENSE MASTERY IN COMPUTER SCIENCE AND MANAGEMENT STUDENTS: IMPLICATIONS FOR LANGUAGE EDUCATION - Kaloeti, Ade Kristianus (ENGLISH JOURNAL, 2025)
The objective of this research is to compare the mastery of English tenses between students majoring in Computer Science and those in Management. This study employs a quantitative methodology with a comparative approach. Utilizing purposive sampling, 20 students from each major were selected to receive instruction on nine English tenses using a uniform teaching method, followed by a comprehension test on the same tenses. The data, derived from test results, were statistically analyzed based on score ranges categorized by frequency, percentage, highest score, lowest score, and average score. The statistical outcomes from both majors were then compared to identify similarities and differences. The findings indicate that Computer Science students demonstrated greater proficiency in the Simple Present, Simple Future, Present Continuous, Present Perfect, and Past Perfect tenses, while Management students excelled in the Simple Future, Present Continuous, Past Continuous, Present Perfect, and Future Perfect tenses. According to the average test scores, Management students outperformed their Computer Science counterparts in nearly all tenses, with the exception of the Past Perfect tense. The difference in tense proficiency between Computer Science students and Management students can primarily be attributed to the nature of their academic training and the skills emphasized in their respective disciplines This research can serve as a foundational reference for English language instructors at the higher education level, applicable to both scientific and non-scientific study programs. By understanding the characteristics and proficiency levels of tense usage across different disciplines, English teachers can adapt their teaching methods accordingly to achieve optimal outcomes.